Islam Wasa?îyah dalam Perspektif Hadis: Dari Konsep Menuju Aplikasi - Ardiansyah, Ardiansyah (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2016)
This article tries to explain the concept of Islamic wasa?îyah (Islamic moderate) from the prophetic ?adîth point of view. It, then, attempts to elaborate the prophet’s attitudes and sayings which have to do with the issue of moderation. It should be noted that many researches have focused more on the polemical ?adîth that are mistreated by some radical Muslims to legitimate their arguments, but are little to investigate the moderation side of the ?adîth. Methodologically, the article employs thematic method to collect ?adîth from the classical book and then analyze it by the contextual frame. By searching of the terminological explanation of moderation, it can be summarized that the prophetic ?adîth has little to say about moderation in term of wasa?îyah, but there has ample of word which is equivalent to the term, that is al-qa?d. Those ?adîth has brought several principles and characteristics, such like al-khayrîyah (chosen), al-‘adâlah (fairness), al-tasâmu? (tolerant attitude), al-tawâzun (balance), al-istiqâmah (consistency), and raf‘ al-?araj (eliminating difficulties). Those principles are significant in terms of demonstrating the peaceful life and arguing the violent and intolerant conducts. The contextual analysis of the ?adîth has argued that those values should be put on the universal principles which Islam has come along with.